PENGARUH EARNING PER SHARE, PRICE EARNING RATIO, INFLASI, SUKU BUNGA, NILAI TUKAR TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nila Aprilia Sukmawati; Mulyanto Nugroho (Journal of Student Research, 2023)
With the development of increasingly modern and rapid economic growth, it is the reason that everyone can make transactions anywhere and anytime, including investment activities carried out in the capital market. Investors must have a lot of careful consideration to invest. This study aims to determine the effect of Earning Per Share, Price Earning Ratio, Inflation, Interest Rates, Exchange Rates on mining companies listed on the Indonesia Stock Exchange in 2017-2022. The method used in this research is a quantitative method. This study used 15 samples of mining sector companies listed on the Indonesia Stock Exchange based on certain criteria. The results of the study found that partially Price earning ratio, inflation, interest rates and exchange rates did not have a significant effect on stock prices, while Earning per share had a positive and significant effect on stock prices.